Currency Redenomination Risk - Kremens, Lukas (Journal of Financial and Quantitative Analysis, 2024)
Abstract A eurozone exit or breakup exposes bondholders to currency redenomination risk. I quantify redenomination risk since the sovereign debt crisis: It contributes substantially to credit spreads around changes in government in France and Italy. Bond prices suggest that markets have priced a potential Italian exit as isolated, and a French one as a breakup. Unlike conventional default risk, redenomination risk can be negative depending on the strength of the national “shadow” currency. Countries with strong shadow currencies earn breakup-insurance premia from the eurozone analog of “exorbitant privilege.” Yield effects are quantitatively large for implied exit probabilities as low as 1%.